CORRECTIVE FEEDBACK AND WRITING ACCURACY OF STUDENTS ACROSS DIFFERENT LEVELS OF GRAMMATICAL SENSITIVITY - Septiana, Ayu Rizki; Sulistyo, Gunadi Harry; Kadarisman, A. Effendi (Indonesian Journal of Applied Linguistics, 2016)
This study investigates whether indirect corrective feedback is effective on students’ writing accuracy and whether there is any interaction between corrective feedback and students’ levels of grammatical sensitivity. A quasi-factorial design was adopted for this research. The subjects of the study were fourth-semester students of English Department, at a State University in Malang, selected randomly. The experimental group was treated with indirect corrective feedback and the control group with direct corrective feedback. A parametric statistical test, ANCOVA, was used to test the hypotheses. The findings show that there was no statistical difference on writing accuracy between the experimental and control groups. Yet, among students with a high level of grammatical sensitivity, there was significant difference in writing accuracy between those given indirect and direct corrective feedback. Further, there was no interaction between corrective feedback on writing accuracy and students’ levels of grammatical sensitivity. However, indirect corrective feedback improved students’ writing accuracy better than direct corrective feedback.